The Influence of @tasyafarasya Influencer Endorsement on Somethinc Skincare Buying Interest - Anindita Nirmala Dewi; Farida Nurfalah; Abdul Jalil Hermawan (International Journal Labs, 2025)
Influencers now often use endorsements as a strategic way on social media platforms to trigger people's buying interest. The purpose of the following study is to determine the influence of Tasya Farasya's influencer endorsement on Instagram @tasyafarasya on the interest in buying Skincare Somethinc. The method applied in this study is non-probability sampling through purposive sampling data collection. A total of 100 respondents participated as observation objects. The quantitative approach is the choice of research method by applying data analysis techniques in the form of simple linear regression tests. The statistical calculation of the t-test resulted in a calculated t-number of 13.549 which is greater than the t of the table of 1.98447, while the significance figure reached 0.000 which was below 0.05, with a positive value coefficient of 0.656. The processing of these numbers proves that H1 is accepted while H0 is rejected, which indicates that the individual influencer endorsement variable has a positive and significant influence on buying interest. The determination coefficient number shows 0.652, which means that influencer endorsements contribute 65.2% to the buying interest variable, while the remaining 34.8% is influenced by various aspects outside of that variable.